Drama and digital arts cultures - Cameron, David; Anderson, Michael 1969-; Wotzko, Rebecca ca. 20. Jh (Methuen drama engage, 2018)
This is a critical guide to the new forms of playful exploration, co-creativity, and improvised performance made possible by digital networked media. Drawing on examples from games, education, online media, technology-enabled performance and the creative industries, the book uses the elements of applied drama to frame our understanding of digital cultures. Exploring the connected real-world and virtual spaces where young people are making and sharing digital content, it draws attention to the fundamental applied drama conventions that infuse and activate this networked culture. Challenging descriptions of drama and digital technology as binary opposites, the book maps common principles and practice grounded in role, embodiment, performance, play, and identity that are being amplified and enhanced by the affordances of online media. Drama and Digital Arts Cultures draws together extensive original research including interviews with game designers, media producers, educators, artists and makers at the heart of these new digital cultures